2011
DOI: 10.1007/s12524-011-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Long-term Urban Expansion of Ranchi Urban Agglomeration, India Using Geospatial Technology

Abstract: The present study analyzes the built-up expansion of Ranchi urban agglomeration over a period of about 8 decades from 1927-2005. Satellite images and topographical maps were used to evaluate land use dynamics during these periods. Built-up growth of 473.7% during 1927-2005 was primarily at the expense of agricultural land along with reduction of natural water bodies reflects negative impacts of built-up expansion, which increased many folds in recent decades. The built-up growth is also analyzed with reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…Thus, more attention should be paid to the drastic expansion of urbanization. Many studies have been conducted worldwide [1], including in regions of Africa [10], Europe [11], Latin America [12], North America [13], and Asia [14][15][16]. Previous studies have also explored the mechanisms of many cities, population and income related to urban and transforming in the process of modernization.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more attention should be paid to the drastic expansion of urbanization. Many studies have been conducted worldwide [1], including in regions of Africa [10], Europe [11], Latin America [12], North America [13], and Asia [14][15][16]. Previous studies have also explored the mechanisms of many cities, population and income related to urban and transforming in the process of modernization.…”
Section: Introductionmentioning
confidence: 99%
“…The high risk areas correspond to high hazard and vulnerability which are extremely prone to flood and also vulnerable to these hazards from point of socio-economic (Pandey et al, 2010). Land use transformation is very useful using satellite data in GIS environment in order to monitor land consumption rate (Kumar et al, 2011). Very significant studies on Kashmir valley lakes (Hamilton and Schaldow, 1997;Subramanium, 2000;Bhatt, 2004;Agarwal et al, 2012) indicated the aspects of high altitude lakes in India.…”
Section: Introductionmentioning
confidence: 99%
“…They mainly focus on the following several aspects. (1) GIS technology and spatial modeling have been widely introduced to investigate landscape change and the spatial patterns of urban expansion (Verburg et al, 1999;Xiao et al, 2006;Liu and Zhang, 2008;Kumar et al, 2011;Wang et al, 2012a;Gao et al, 2013;Mondal et al, 2015;Zeng et al, 2015;Zhao et al, 2015). For example, Xiao et al (2006) categorized spatial patterns into special objectives, social-political intervention, and normal urban growth.…”
Section: Introductionmentioning
confidence: 99%